THE EFFECT OF LEARNING BY GAMES AND STORYTELLING LEARNING METHODS ON MATHEMATICAL NUMERACY LITERACY SKILLS IN GRADE V ELEMENTARY SCHOOLS - Ardiyanti, Fenty; Habiby, Wahdan Najib (Universitas Muhammadiyah Mataram, 2025)
This study investigates how learning through games and narrative affects Year 5 students' mathematical literacy and numeracy skills. The study's goal is to solve Indonesia's poor performance in international math literacy examinations by testing new teaching approaches. The study included three groups: one using games, one using narrative, and one combining the two modalities. Data were gathered through teacher interviews, observations, and validated numeracy literacy assessments. These results were examined utilizing quantitative quasi-experimental procedures, using pretest-posttest control groups. The findings show that games and storytelling greatly improve pupils' arithmetic literacy and numeracy when compared to traditional methods. The combined strategy yielded the best improvement, improving problem-solving and conceptual knowledge through interactive, contextualized learning, which increases motivation and critical thinking skills. The study concludes that incorporating games and storytelling effectively promotes mathematical comprehension, and teachers are encouraged to use these strategies to create more engaging and relevant math learning environments for primary school students, better preparing them for future academic challenges.